Micromorphology of Restorative System-Dentin Interface in Primary Teeth Using Different Adhesive Systems and Burs - Tereza Cristina Favieri de MELO-SILVA; Silvio Issao MYAKI; Claudio Luis de MELO-SILVA; Victor Elias ARANA-CHAVEZ; José Eduardo Junho de ARAÚJO (Association of Support to Oral Health Research (APESB), 2007)
Objective: This study in vitro evaluated the micromorphology of the resin-dentin interface in primary teeth, using different rotatory instruments and adhesive systems. Method: Twenty primary molars were selected and randomly divided into two groups (n=10). In group C, the occlusal surfaces of teeth were cut with a carbide bur at high-speed until the area of dentin exposure. In group D, the same procedure was conducted, but the dentin was cut with a diamond bur. The surface of each tooth was divided into two halves; one half of the occlusal surface received application of two-step total-etch adhesive system (Single-Bond - 3M), and the other half received application of one-step self-etching adhesive (One Up Bond F - Tokuyama). All teeth were restored with composite (Z-250 - 3M). The samples were thermocycled, embedded in acrylic resin, sectioned for achievement of the resin-dentin interface and the teeth were sputter- coated with gold and observed under SEM. Results: the two adhesive systems showed hybrid layer formation; the two-step adhesive system demonstrated better interface sealing than the self-etching; the dentin cut with carbide burs was not statistically different with regard to the adhesive system; and diamond bur with self-etching adhesive system showed the worst interface sealing with the highest gap values. Conclusion: the diamond bur presented negative influence only in the quality of the interface between restorative system and primary dentin when it was used the one step self-etching adhesive system.